The Effectiveness of Ergonomic Intervention in Work-related Postures and Upper Crossed Syndrome of Metal Industry Workers - Hosseini, Seyed Mohammad; Lahoori, Mohammad Armin; Rasouli Kahaki, Zeinab (La Medicina del Lavoro, 2025)
Introduction: Upper Crossed Syndrome (UCS) is a musculoskeletal disorder that mainly occurs due to awkwardposture in a static position. Considering the impact of musculoskeletal disorders on individual and social life, and the limited studies carried out in metal industries, this study evaluated the effect of ergonomic interventions using engineering controls on work-related postures and skeletal abnormalities caused by UCS in one of the metal industries. Methods: In this interventional study, 132 welders, press, and warehouse workers who had symptoms related to UCS were included. There were 78 participants in the experimental group (43 welders and 35 press operators) and 54 warehouse workers in the control group. Sitting and standing workstations were evaluated using the RULA and REBA methods, respectively. Then, with the technical committee's decision, the necessary ergonomics interventions were carried out. After three months of applying the interventions, the postures were re-evaluated. The paired t-test method was used for intra-group evaluation, and the independent t-test was used to compare the experimental and control groups using SPSS. Result: This study showed that ergonomic interventions can significantly reduce the risk score of musculoskeletal disorders in different body segments in sitting and standing workstations. Examining the UCS of the experimental group with sitting activities after the intervention, the average angle of the forward head, round shoulder, and kyphosis was reduced by 3.89, 4.05, and 3.73 degrees, and with standing activities by 3.27, 2.70, and 3.10 degrees, respectively. Conclusion: The results of the study revealed that modifying the workstation has a significant role in reducing the UCS.